Mast cell‐derived serotonin enhances methacholine‐induced airway hyperresponsiveness in house dust mite‐induced experimental asthma. Issue 7 (9th March 2021) - Mendez‐Enriquez, Erika; Alvarado‐Vazquez, Perla Abigail; Abma, Willem; Simonson, Oscar E.; Rodin, Sergey; Feyerabend, Thorsten B.; Rodewald, Hans‐Reimer; Malinovschi, Andrei; Janson, Christer; Adner, Mikael; Hallgren, Jenny
Abstract: Background: Airway hyperresponsiveness (AHR) is a feature of asthma in which airways are hyperreactive to stimuli causing extensive airway narrowing. Methacholine provocations assess AHR in asthma patients mainly by direct stimulation of smooth muscle cells. Using in vivo mouse models, mast cells have been implicated in AHR, but the mechanism behind has remained unknown. Methods: Cpa3 Cre /+ mice, which lack mast cells, were used to assess the role of mast cells in house dust mite (HDM)‐induced experimental asthma. Effects of methacholine in presence or absence of ketanserin were assessed on lung function and in lung mast cells in vitro . Airway inflammation, mast cell accumulation and activation, smooth muscle proliferation, and HDM‐induced bronchoconstriction were evaluated. Results: Repeated intranasal HDM sensitization induced allergic airway inflammation associated with accumulation and activation of lung mast cells. Lack of mast cells, absence of activating Fc‐receptors, or antagonizing serotonin (5‐HT)2A receptors abolished HDM‐induced trachea contractions. HDM‐sensitized mice lacking mast cells had diminished lung‐associated 5‐HT levels, reduced AHR and methacholine‐induced airway contraction, while blocking 5‐HT2A receptors in wild types eliminated AHR, implying that mast cells contribute to AHR by releasing 5‐HT. Primary mouse and human lung mast cells express muscarinic M3 receptors. Mouse lung mast cells store 5‐HT intracellularly, and methacholine induces release of 5‐HT from lung‐derived mouse mast cells and Ca 2+ flux in human LAD‐2 mast cells. Conclusions: Methacholine activates mast cells to release 5‐HT, which by acting on 5‐HT2A receptors enhances bronchoconstriction and AHR. Thus, M3‐directed asthma treatments like tiotropium may also act by targeting mast cells. Abstract : Lung mast cells expand and release mediators in mice with HDM‐induced experimental asthma, and ketanserin (antagonizing 5‐HT2A receptors) blocks HDM‐induced increased airway resistance to MCh in vivo . Mast cell deficient Cpa3 Cre/+ mice show decreased HDM‐induced airway resistance to MCh in vivo (AHR), reduced contraction of airways to MCh ex vivo, and have impaired lung‐associated 5‐HT levels. Lung mast cells express muscarinic M3 receptors and respond to MCh by releasing 5‐HT, which likely acts on nerves to release ACh, thereby enhancing the contraction of bronchioles and AHR. Abbreviations: ACh, acetylcholine; AHR, airway hyperresponsiveness; Cpa3, carboxypeptidase A3; 5‐HT, serotonin; HDM, house dust mite; M3, muscarinic receptor 3; MC, mast cell; MCh, methacholine; MCp, mast cell progenitor; PCLS, precision‐cut lung slices.